The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/2045-5380-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased default mode network activity in socially anxious individuals during reward processing

Abstract: BackgroundSocial anxiety has been associated with potentiated negative affect and, more recently, with diminished positive affect. It is unclear how these alterations in negative and positive affect are represented neurally in socially anxious individuals and, further, whether they generalize to non-social stimuli. To explore this, we used a monetary incentive paradigm to explore the association between social anxiety and both the anticipation and consumption of non-social incentives. Eighty-four individuals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Some studies showed that during pain expectation, the precuneus and PCC were deactivated in HCs and exhibited decreased activation associated with expected pain intensity . People with anxiety had increased precuneus activity during reward anticipation, suggesting that these subjects were unable to disengage from self‐attention, leading to increased self‐focused hypervigilance . When viewed together, these reports are in line with the current findings that IBS subjects showed activation of the PCC and precuneus while HCs showed deactivation of these regions in response to contextual threat.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies showed that during pain expectation, the precuneus and PCC were deactivated in HCs and exhibited decreased activation associated with expected pain intensity . People with anxiety had increased precuneus activity during reward anticipation, suggesting that these subjects were unable to disengage from self‐attention, leading to increased self‐focused hypervigilance . When viewed together, these reports are in line with the current findings that IBS subjects showed activation of the PCC and precuneus while HCs showed deactivation of these regions in response to contextual threat.…”
Section: Discussionsupporting
confidence: 90%
“…49 People with anxiety had increased precuneus activity during reward anticipation, suggesting that these subjects were unable to disengage from self-attention, leading to increased self-focused hypervigilance. 65 When viewed together, these reports are in line with the current findings that IBS subjects showed activation of the PCC and precuneus while HCs showed deactivation of these regions in response to contextual threat. The salience network has been suggested to play a role in switching between the default mode network and task-related networks.…”
Section: Disease-related Differences In Brain Responsessupporting
confidence: 89%
“…This finding has been extended to subclinical social‐anxiety . Another study found increased DMN activity during the anticipation of monetary reward . The DMN has typically been established in resting‐state fMRI studies, and several aberrant functional connectivity patterns with or within the DMN have been found although not consistently .…”
Section: The Emotion Networkmentioning
confidence: 93%
“…Recent results suggest that social reward responsivity to reward valuation in patients with social anxiety disorder may be reduced as reflected by diminished activity in putamen and reduced ventral striatal-anterior cingulate cortex connectivity (Cremers, Veer, Spinhoven, Rombouts, & Roelofs, 2014). However, these effects may be specific to social reward cues and not apply to monetary rewards (Maresh, Allen, & Coan, 2014). Contingency learning in anxiety has received little attention from researchers.…”
Section: Empirical Indicationsmentioning
confidence: 99%